Correlation between working position of dentists and malondialdehyde concentration with musculoskeletal complaints - Hari Wibowo (Faculty of Dental Medicine Universitas Airlangga, 2017)
Background: Musculoskeletal complainstof dentists have become common issues in dentistry since the awkward positions during treating the patients; such as position of a dentist who bends towards the patient, moving abruptly, twisting the body from a side to another side. All those movements are done several times in long term. Such high level of activity without sufficient recovery time may lead to an oxidative stress, so it will affect on the musculoskeletal and concentration of malondialdehyde (MDA) in blood. Purpose: The purpose of this study was to identify the correlation between MDA concentration on the risk of musculoskeletal complaint on dentist with working position of maxilla dental patching at community health center(Puskesmas) in Surabaya. Method: This study was observational analytics using cross sectional approach with cluster random sampling technique. The total samples were 19. Musculoskeletal complains assesment is conducted using a Nordic body map questionaire that devided into 4 scores. Working position of samples were asseses using Ovako working posture analysis (OWAS). Bloos sampling was conducted to examine the concentration of MDA. Result: From data analysis result using Spearman correlation test, it was found that there was a significant correlation between working position and musculoskeletal complaint using Spearman correlation test and the p value obtained was<0.05. This research also found that there was a significant correlation between malondialdehyde concentration and musculoskeletal complaint using Pearson correlation test and the p value obtained was <0.05. Conclusion: There was a correlation between working positions of dentists and musculoskeletal complaints. There was a correlation between working position and MDA concentration with the musculoskeletal complaints.